Pengaruh latihan el rondo terhadap akurasi passing pada permainan sepak bola - Nugraha, Ilham Jaya; Safari, Indra; Mulyanto, Respaty (Universitas Hamzanwadi, 2024)
The problem found in the soccer extracurricular of SDN Situraja is that there are still many extracurricular members who are not precise in passing when playing soccer games, so that the direction of the ball from the passing is often out of the playing field area or captured by the opponent. This study aims to examine the results of el rondo training on passing accuracy in extracurricular soccer members. The research method used is quantitative pre-experiment with a pretest posttest one group design. The population is Situraja elementary school students totaling 120 students. The sample selection technique used was purposive sampling and the sample was 20 students. Data analysis using the statistical product for social science (SPSS) 26 program. Data analysis in this study uses quantitative data analysis, namely the process of organizing, interpreting and analyzing data quantitatively, which quantitative data analysis uses statistical analysis techniques paired sample T test. The result is the pretest passing value of 0.951 with sig. 0.263 > 0.05 thus the sample data is normal. While the posttest passing value is 0.950 with sig 0.362 > 0.05 thus the sample data is normal. So it can be concluded Hi accepted, which means that in this study there is an influence.